Penerapan Metode Simple Additive Weighting Untuk Pengalokasian Anggaran Dana Bantuan Operasional Sekolah - Fricles A Sianturi (Jurnal Sains dan Teknologi, 2021)
School Operational Assistance (BOS) is a government program that is basically providing funding for non-personnel operating costs for basic education units as implementing compulsory education programs. With the existence of BOS funds, it is hoped that education can succeed in Indonesia and produce a quality generation of the nation. The ineffectiveness of the management and allocation of BOS funds is one of the problems in the world of education. Therefore we need a Decision Support System that can help schools allocate BOS funds with the Simple Additive Weighting (SAW) method. The SAW method is often known as the weighted sum method by determining the value of each criterion for each selected alternative. This funding allocation decision support system was also applied using the Microsoft Visual Studio 2010 programming language and by using the Microsoft Access 2010 database. The results of this study were obtained for Quarter I namely Alternative A4, for Quarter II namely Alternative A3, for TW III namely Alternative A1 , and for Quarter IV alternative A5.